DESENVOLVIMENTO E PROTOCOLO DE AVALIAÇÃO DO PROGRAMA DE INTERAÇÃO PARA PAIS - PIPA - FALCÃO, Michelle Rodrigues de Siqueira (2024)
The arrival of a child introduces a new context into the parents' lives and demands different ways of acting. Parents are faced with situations that pose a challenge in their children's education and life experience is not always enough to learn how to educate and establish a healthy relationship. On the other hand, Parent Training - TP is defined as a set of procedures in which parents or caregivers are trained to modify their disciplinary and educational practices and, consequently, to act on the unwanted behavioral pattern of their children. Literature findings have pointed to this intervention as promising in the development of healthy parenting practices. In this sense, the general objective of this study is to develop and describe a protocol for evaluating the results of a PT from a behavioral-analytic perspective and as specific to present a program with objectives, sample, instruments and resources and procedures of a PT for a population not clinic and develop a protocol for evaluating PT results to verify the effects on modifying interactions between parents and children. To prepare the TP, it was necessary to characterize and analyze national TPs, as well as their potential and limitations. The TP that will be presented was called PIPA, designed for a group of eight parents, of both sexes, with children aged 6 to 13 years. It consists of eight meetings lasting an average of 1 hour and 30 minutes. The themes will be discussed from a behavioral-analytic perspective. To evaluate results, it is proposed to analyze direct and indirect measures of behavior, both from parents and children. It is expected that it will contribute to improving educational practices and family interaction. It concludes by pointing out the importance of parents in children's behavioral development and the commitment of behavior analysts to presenting evidence-based practices.